Grafted tomatoes tolerate heat and waterlogging - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Farmers in the tropics can now grow tomatoes all the year round. This is achieved by grafting young tomato plants onto an eggplant rootstock which enables them to withstand high temperatures and waterlogged soils. During periods of the tropical...